2020
DOI: 10.1155/2020/8835627
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Therapeutic Anticoagulation in COVID-19

Abstract: Coagulopathy has proven to be a common complication of the novel coronavirus SARS-CoV-2, with evidence of elevated D-dimers and fibrin degradation products associated with an increased incidence of thromboembolism. Despite emerging evidence describing the coagulopathy and its clinical relevance in COVID-19, fewer studies have addressed the potential role of empiric therapeutic anticoagulation in this setting. We report the case of a patient admitted to our intensive care unit (ICU) with severe acute respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Besides, previous studies supported anticoagulant application as both therapy and prophylaxis. Anticoagulants potentially decrease coagulopathy, microthrombus, and organ damage ( 16), but there are still no general guidelines for their application in COVID-19 patients, and further studies are required to ensure effectiveness (17).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, previous studies supported anticoagulant application as both therapy and prophylaxis. Anticoagulants potentially decrease coagulopathy, microthrombus, and organ damage ( 16), but there are still no general guidelines for their application in COVID-19 patients, and further studies are required to ensure effectiveness (17).…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Treatment with LMWH within the initial 7-day onset of acute respiratory distress syndrome significantly improved the PaO 2 /FiO 2 ratio and reduced the risk of 7-day mortality by 48% and the risk of 28-day mortality by 37%, particularly in the subgroup receiving high-dose LMWH (≥5000 U/day). [ 23 ] However, the largest available study to date evaluating anticoagulation was an analysis of 2773 patients with Covid-19 in the Mount Sinai Health System. Here, the authors found that patients who received anticoagulation were significantly more likely to require invasive mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of postmortem autopsies found that PE was the direct cause of death (33%) [22] . Treatment with LMWH within the initial 7-day onset of acute respiratory distress syndrome significantly improved the PaO 2 /FiO 2 ratio and reduced the risk of 7-day mortality by 48% and the risk of 28-day mortality by 37%, particularly in the subgroup receiving high-dose LMWH (≥5000 U/day) [23] . However, the largest available study to date evaluating anticoagulation was an analysis of 2773 patients with Covid-19 in the Mount Sinai Health System.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of post-mortem autopsies found that pulmonary embolism(PE) was the direct cause of death in 4 (33%) [17]. Treatment with LMWH within the initial 7-day onset of acute respiratory distress syndrome (ARDS) signi cantly improved the PaO2/FiO2 ratio and reduced the risk of 7-day mortality by 48% and the risk of 28-day mortality by 37%, particularly in the subgroup receiving high-dose LMWH of ≥ 5000U/day [18]. However, the largest available study evaluating anticoagulation was an analysis of 2,773 patients with COVID-19 in the Mount Sinai Health System found that patients who received anticoagulation were signi cantly more likely to require invasive mechanical ventilation [19].Our results showed that LMWH therapy could reduce PCO2, which was considered to be related to reduction of pulmonary vascular thrombosis and improvement in alveolar-capillary gas exchange.…”
Section: Discussionmentioning
confidence: 99%